2013
DOI: 10.1093/jac/dkt180
|View full text |Cite
|
Sign up to set email alerts
|

Predicting antimicrobial susceptibilities for Escherichia coli and Klebsiella pneumoniae isolates using whole genomic sequence data

Abstract: ObjectivesWhole-genome sequencing potentially represents a single, rapid and cost-effective approach to defining resistance mechanisms and predicting phenotype, and strain type, for both clinical and epidemiological purposes. This retrospective study aimed to determine the efficacy of whole genome-based antimicrobial resistance prediction in clinical isolates of Escherichia coli and Klebsiella pneumoniae.MethodsSeventy-four E. coli and 69 K. pneumoniae bacteraemia isolates from Oxfordshire, UK, were sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
219
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(237 citation statements)
references
References 32 publications
13
219
1
1
Order By: Relevance
“…By providing definitive genotype information, WGS offers the highest practical resolution for characterizing an individual microbe. This includes the full complement of resistance determinants (7,8), including resistance to compounds not routinely tested phenotypically. Bacteria that have identical resistance patterns caused by different mechanisms can also be differentiated by WGS.…”
mentioning
confidence: 99%
“…By providing definitive genotype information, WGS offers the highest practical resolution for characterizing an individual microbe. This includes the full complement of resistance determinants (7,8), including resistance to compounds not routinely tested phenotypically. Bacteria that have identical resistance patterns caused by different mechanisms can also be differentiated by WGS.…”
mentioning
confidence: 99%
“…Recent studies have shown that WGS analysis can potentially be a single, rapid, and cost-effective approach to define resistance genotypes and predict resistance phenotypes of bacteria with great sensitivity and specificity (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…For most bacteria, the evidence for using WGS to infer antimicrobial susceptibility data is sparse, although some studies have shown a high correlation between resistance phenotypes and the presence of resistance genes or resistance-associated mutations. This agreement has been best demonstrated with enteric bacteria, including Escherichia coli, Campylobacter spp., and nontyphoidal Salmonella (8)(9)(10)(11)(12). In addition, other DNAbased methods have been used to detect resistance determinants and even guide therapy for infections caused by Mycobacterium tuberculosis, Staphylococcus aureus, HIV, and other pathogens (13)(14)(15).…”
mentioning
confidence: 99%